2001
DOI: 10.1042/0264-6021:3580447
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear localization and mitotic phosphorylation of HIRA, the human homologue of Saccharomyces cerevisiae transcriptional regulators Hir1p/Hir2p

Abstract: The HIRA gene encodes a nuclear protein with histone-binding properties that have been conserved from yeast to humans. Hir1p and Hir2p, the two HIRA homologues in Saccharomyces cerevisiae, are transcriptional co-repressors whose action resides at the chromatin level and occurs in a cell-cycle-regulated fashion. In mammals, HIRA is an essential gene early during development, possibly through the control of specific gene-transcription programmes, but its exact function remains to be deciphered. Here we report on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…More specifically, these phosphorylation events may negatively regulate the ability of Gro/TLEs to interact with components of chromatin and/or the nuclear matrix, thereby playing a negative regulatory role in Gro/TLE functions. Such a model is consistent with the observation that mitotic phosphorylation events decrease the interaction with chromatin of another mammalian protein, termed HIRA, that is structurally related to Gro/TLEs and is also involved in transcriptional repression (42).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…More specifically, these phosphorylation events may negatively regulate the ability of Gro/TLEs to interact with components of chromatin and/or the nuclear matrix, thereby playing a negative regulatory role in Gro/TLE functions. Such a model is consistent with the observation that mitotic phosphorylation events decrease the interaction with chromatin of another mammalian protein, termed HIRA, that is structurally related to Gro/TLEs and is also involved in transcriptional repression (42).…”
Section: Discussionsupporting
confidence: 71%
“…After this time, mitotically enriched cells that were loosely attached or floating were collected by gentle pipetting, whereas adherent cells were not collected. This protocol was shown to yield greater than 80% of cells with a DNA content corresponding to the G 2 /M phase, with most of these cells being in mitosis (42). Cultures enriched for cells arrested at the G 1 /S transition were obtained by treatment with 10 mM hydroxyurea (41), followed by removal of floating or loosely attached cells and recovery of the strongly adherent cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we showed that ectopic expression of HIRA inhibited DNA synthesis and arrested cells in S phase of the cell cycle (21). De Lucia and coworkers showed that HIRA is phosphorylated during mitosis and that phosphorylation is accompanied by release from nuclear chromatin (11). HIRA has been shown to interact with several proteins implicated in control of transcription and nuclear structure, including Pax3 and histones (36,40).…”
mentioning
confidence: 99%
“…The role of Hira in higher eukaryotes is not known, but the protein is localized to the nucleus where a proportion is associated with the nuclear matrix (15). Hira is a target for cdk2/ cyclin E phosphorylation, and ectopic expression of Hira can block cells in the S phase of the cell cycle (22).…”
mentioning
confidence: 99%